Surveillance of child development: practices of nurses after training - Altamira Pereira da Silva Reichert; Vanessa Medeiros Nóbrega; Simone Soares Damasceno; Neusa Collet; Sophie Helena Eickmann; Marília Carvalho Lima (Universidade Federal de Goias, 2015)
The aim of this study was to evaluate the perception of nurses regarding their practice in child care after training in child development surveillance, in the context of the Integrated Care for Childhood Prevalent Diseases. An exploratory study, using a qualitative approach, was developed between June and August 2009, by means of interviews with 11 nurses who participated in training workshops developed in João Pessoa, Paraíba, Brazil. The thematic analysis helped identify three categories: weaknesses in child development surveillance before training; post-training qualified perspective: professional motivation and empowerment; and a new behavior in child development surveillance. The training was considered to be a powerful strategy for professional qualification and for changing the attitude of primary care nurses, motivating nurses to adopt a new behavior in child development surveillance.